Peran Lingkungan Rumah Sebagai Safe Space dalam Menunjang Keberhasilan Akademik Anak - Sarah Azka Fiddaroin; Ellen Prima (INDO PUBLISHING, 2026)
A child's academic success is not only determined by factors at school, but is also greatly influenced by the home environment. In this article, we will examine how the home environment functions as a safe space to help children excel in school. The concept of safe space here goes beyond physical safety to psychological and emotional safety, where children feel accepted, valued, and have the freedom to speak without fear of judgment. It has been proven that a stable and supportive home environment can reduce stress and distractions. This allows children to focus on their studies and participate more actively in school.